A presença feminina na Faculdade de Direito de Pelotas - RS - Costa, Valesca Brasil (2009)
This work named The feminine presence in Pelotas-RS Law School , developed in the Education Faculty of Pelotas, research group History of Education, it is a study that is intimately connected to my life, for I am graduated in Law and in the juridical environment I captured a praxis that even silently drew differences between men and women in a place of a profession known as typically masculine. In the first part of the research we did the bibliographic review. The second part took place in the Law School of Pelotas, specifically the Academic Center Ferreira Viana, the School Library and the Public Library of Pelotas where we did some work with archives, journals, books, cassette tapes. During the research we realized that was no objections to feminine presence in the faculty as it is written in the Article 49 from the Law School statute of 1929. So I decided to start the master‟s dissertation research by that information and found out that the first woman student in Pelotas Law School was Cilulia de Freitas, who has entered the faculty in 1921, daughter of a Law Judge, intended to follow her father‟s professional steps but coursed until the fourth year when she decided to quit Law School to marry a class mate. Although it is only in the year 1936 that we have the first women graduated in Pelotas Law School: Heloisa Assumpção, Sophia Galanternick e Maria Adali. Women that besides being pioneers in the juridical area also stud out in their career. Rosah Russomano also stands out for her discourse as spokeswoman of the class of 1947, being one of the three women in a class with 9 men and pointing out in her speech the situation of women in that society. We must also remember Gilda Corrêa Meyer Russomano, graduated in 1951, which were awarded as student and became teacher of International Public Law in the Law School of Pelotas. This research also proposes to rescue other feminine figures that stud out in Pelotas Law School and inside the juridical area. In this way, when we aim our study to the first women students that coursed Law School in Pelotas we are not only recovering the historical past of Law School in that city, but also we are thinking about social relationships that limited the presence of women in decisive society roles. When writing about the women in the city of Pelotas who made an option on the juridical world, we may also say that those women were an example and a demonstration that education is a valuable instrument for women to be part of society as a important subject, directly participating on the decisions and social construction.